Patient-Level, Institutional, and Temporal Variations in Use of Imaging Modalities to Confirm Pulmonary Embolism. (16th May 2020) - Mehdipoor, Ghazaleh; Jimenez, David; Bertoletti, Laurent; Fidalgo, Ángeles; Sanchez Muñoz-Torrero, Juan Francisco; Gonzalez-Martinez, José Pedro; Blanco-Molina, Ángeles; Ángel Aibar, Miguel; Bonnefoy, Pierre-Benoît; Khorasani, Ramin; Prince, Martin R.; Bikdeli, Behnood; et al.
Abstract : Background: The choice of the imaging modality for diagnosis of pulmonary embolism (PE) could be influenced by provider, patient or hospital characteristics, or over time. However, little is known about the choice of the diagnostic modalities in practice. The aim of this study was to evaluate the variations in the use of imaging modalities for patients with acute PE. Methods: Using the data from Registro Informatizado Enfermedad TromboEmbolica (RIETE), a prospective international registry of patients with venous thromboembolism (March 2001–January 2019), we explored the imaging modalities used in patients with acute PE. The imaging modalities included computed tomography pulmonary angiography, ventilation/perfusion scanning, pulmonary angiography, a combination of these tests, or PE signs and symptoms plus imaging-confirmed proximal deep vein thrombosis but no chest imaging. Results: Among 38 025 patients with confirmed PE (53.1% female, age: 67.3±17 years), computed tomography pulmonary angiography was the dominant modality of diagnosis in all RIETE enrollees (78.2% [99% CI, 77.6–78.7]); including pregnant patients (58.9% [99% CI, 47.7%–69.4%]) and patients with severe renal insufficiency (62.5% [99% CI, 59.9–65.0]). A greater proportion of patients underwent ventilation/perfusion scanning in larger hospitals compared with smaller hospitals (13.1% versus 7.3%, P <0.001). The use of computed tomography pulmonary angiography varied between 13.3% and 98.3% across the countries, and its use increased over time (46.5% in 2002 to 91.7% in 2018, P <0.001). Conclusions: In a large multinational PE registry, variations were observed in the use of imaging modalities according to patient or institutional factors and over time. However, computed tomography pulmonary angiography was the dominant modality of diagnosis, even in pregnancy and severe renal insufficiency. The safety, costs, and downstream effects of these tests on PE-related and non-PE-related outcomes warrant further investigation. Abstract : Supplemental Digital Content is available in the text.